2016
DOI: 10.1021/acs.jafc.6b03286
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Iron Availability from Insects and Sirloin Beef

Abstract: Interest in the consumption of insects (entomophagy) as an alternative environmentally sustainable source of protein in the diet of humans has recently witnessed a surge. Knowledge of the nutrient composition and, in particular, the bioavailability of minerals from insects is currently sparse. This study evaluated the availability of Fe, Ca, Cu, Mg, Mn, and Zn from four commonly eaten insects and compared these to sirloin beef. Soluble iron from the samples was measured by inductively coupled plasma optical em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 23 publications
6
70
1
2
Order By: Relevance
“…Iron content of insects also has higher solubility rate than that derived from beef (Latunde-Dada, Yang, & Vera Aviles, 2016). Iron and calcium contents are lower than the average value of both minerals in insects and beef analyzed by Latunde-Dada et al (2016). According to Oonincx and van der Poel (2011), the mineral content of insects depends on the type of food.…”
Section: F Mineralmentioning
confidence: 88%
See 1 more Smart Citation
“…Iron content of insects also has higher solubility rate than that derived from beef (Latunde-Dada, Yang, & Vera Aviles, 2016). Iron and calcium contents are lower than the average value of both minerals in insects and beef analyzed by Latunde-Dada et al (2016). According to Oonincx and van der Poel (2011), the mineral content of insects depends on the type of food.…”
Section: F Mineralmentioning
confidence: 88%
“…Insects are not only able to provide adequate protein and energy and meet the needs of the amino acids that humans require, but also provide unsaturated fatty acids in the form of mono-and poly-unsaturated fatty acids that are good for the body and rich (Rumpold & Schlüter, 2013). Insects also contain iron in sufficient quantities to overcome the problem of anemia due to deficiency of mineral Fe (Latunde-Dada et al, 2016). Result shows that insects are very worthy to be utilized as much as possible to fulfill human needs of food, especially as an alternative source of animal protein.…”
Section: F Mineralmentioning
confidence: 99%
“…For example, one study examined the bioavailability of iron in maize‐field grasshopper ( Sphenarium purpurascens) , black crickets ( Gryllus bimaculatus ), mealworms ( Tenebrio molitor ) and buffalo worms ( Alphitobius diaperinus) . Buffalo worms and sirloin meat were found to have the highest levels of iron bioavailability, with buffalo worms slightly higher than sirloin meat, while the other insects displayed a mid‐range of iron bioavailability between the highest and lowest samples (whole wheat) tested (Latunde‐Dada & Yang ). It should be noted these in vitro studies of a Caco‐2 cell model and no human or animal trials have been conducted to date.…”
Section: Opportunitiesmentioning
confidence: 98%
“…; Orthoptera: Pyrgomorphidae), and two-spotted crickets (Gryllus bimaculatus Geer; Orthoptera: Gryllidae) (56) . In the same study by Latunde-Dada et al (56) , it was shown that the addition of insects to wheat flour (1:1) was superior to beef in increasing Fe and Zn solubility in the composite mixtures. Based on the above, it is likely that the addition of insects to current starch-based diets, exemplary for individuals living in many low-and middle-income countries (LMIC), will provide additional Fe and Zn, that could potentially fill the requirement gap, and maybe increase the bioavailability of native and fortification Fe in the starchy foods.…”
Section: Bioavailability Of Iron and Zinc In Insect-derived Foodmentioning
confidence: 99%